Literature survey of automatic face recognition system and eigenface based implementation - Ferdous, Shariful Islam; Ahmed, Sabbir (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.